SIGNIFIED BY THE WORD WAY (Literary activity of Les Kurbas) - Khorob, Stepan (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2023)
The purpose of the article is to examine literary activity of the director of Ukrainian stage art Les Kurbas as a collective and integral system of his views on drama as a genre of literature and a form of art, on the specifics of its stylistic dominants in the first decades of the 20th century through the prism of the reformist ideas. The object of the research is the prose attempts of the Ukrainian theater actor, his translated works and scientific works, his stagings based on the works of Ukrainian and foreign authors, and his theatrical journalism - the director’s diary, lectures on directing and stage practice. The methodological basis of the research is the biographical method, the principles of cultural-historical and hermeneutic methods, as well as the principles of the comparative-typological approach in the analysis of the object and subject of the study. The scientific novelty of the article lies in the complex and systematic clarification of the problem "Les Kurbas and literature", as a result of which it is proved that the brilliant Ukrainian director began his work with verbal art (he debuted as a novelist), during his directorial activity as the artistic director of the "Molodyi Teatr", "Kyidramte" and "Berezol" staged lyrical and epic works of Ukrainian and foreign writers several times (he worked as a playwright), translated plays of Western European authors, scientific studies of art critics from Europe (acted as a translator), often studied as a director the emergence of certain modernist currents through the prism of literature and theater (positioned himself as a literary critic and researcher of drama). Such a multifaceted connection of Les Kurbas with literary and artistic creativity, with scientific and research activity gives reason to conclude that throughout his creative life he was closely connected with the word and was consistently realized in the word. The practical significance of the research lies in the fact that its results can be used by both theater scholars and theorists and historians of Ukrainian and foreign literature.